Expression characteristics of circular RNA in human traumatic brain injury - Li, Zhenxing; Lin, Yixing; Mao, Lei; Zhang, Li (Frontiers in Neurology, 2023)
Traumatic brain injury (TBI) causes high rates of worldwide mortality and morbidity due to the complex secondary injury cascade. Recently, circular ribonucleic acids (circRNAs) have attracted significant attention in a variety of diseases. However, their expression characteristics in human TBI are still unclear. In this study, we examined brain injury tissues from six severe TBI patients in Jinling Hospital. The TBI tissues and adjacent brain contusion tissues were used to analyze differential expression signatures of circRNAs through full-length transcriptome sequencing, Gene Ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and ceRNA network construction. Our results found that there were 126 differently expressed circRNAs in TBI. Among them, 64 circRNAs were up-regulated and 62 circRNAs were down-regulated. Moreover, GO and KEGG analyses revealed that the aberrantly expressed circRNAs participated in many pathophysiological processes of TBI, especially regarding microglial cell activation, protein transport, protein processing and inflammation. Furthermore, the ceRNA (circRNA-miRNA-mRNA) network predicted that there existed strong relationship among circRNA, miRNA and mRNA. Taken together, our results indicated for the first time that the expression profiles of circRNAs were different after human TBI. In addition, we found the signaling pathways that were related to circRNAs and predicted a ceRNA network, which provided new insight of circRNAs in human TBI.